SPECIAL PROGRAMS FOR THE GIFTED: A CRITIQUE OF SOME ARGUMENTS - Cassivi, Denis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
Concern that the more gifted children are not getting due attention is one of the current novelties in the shop-window of educational discussion. The issue has some genuine challenge and significance for education; but a commodity that has been in short supply for some time and for which the public has acquired a genuine appetite is in serious danger of being too eagerly pulled from the oven halfbaked. Denis Cassivi here performs a service ail too rarely offered in education, a timely and comprehensive critique of an emerging fad, with the object not of destroying it but of saving it. By raising questions about the assumption that special education is needed for special groups, his arguments anticipate some of the problems to which the Journal's next issue, on "Special Education," will address itself.